Recent advances in nanoparticle carriers for photodynamic therapy - Yi, Gawon (Quant Imaging Med Surg, 2018)
This review summarizes recent advances in the development of nanoparticles (NPs) for efficient photodynamic therapy (PDT), particularly the development and application of various NPs based on organic and inorganic materials. PubMed database was used for literature search with the terms including NP, nanomedicine, PDT, photosensitizer (PSs), and drug delivery. For successful PDT, it is essential to deliver PSs to target disease sites. A number of NPs have been developed and tested as the carriers for both imaging and therapy, an approach termed “nanomedicine”. Many studies of NP carriers showed increased water solubility and stability of PSs for in vivo injection, and these NP carriers provided benefits including longer circulation in blood and higher accumulation of PSs at disease sites. This review describes new techniques in PDT such as aggregation-induced emission (AIE) and luminescence-based PDT, and provides insights on NPs and PDT for biomedical researchers working to develop or apply NPs in efficient PDT.